Stages of Faith Development According To The Theory of James W Fowler On The Process of Human Religious Development (Analysis of The Development of Religion In Elementary-Adult Children) - Faizah Naily (Insight School Academy, 2023)
We need to instill faith basics in children from an early age . Allah commands everyone to believe in Him. This study aims to analyze the development of religion that occurs in human life from elementary school age to adults. The author uses James W Fowler's theory for this research regarding the stages of human faith from an early age to adulthood. Therefore, the writer intends to analyze the development of human religion. This study used a qualitative approach, which emphasized descriptive analysis based on the documents obtained and the results of interviews with respondents. The data sources for this research consisted of primary and secondary data, which were then analyzed using various papers and interview results. The findings from this study indicate that the development of religion and diversity in humans has existed since birth . And humans will continue to develop in the social, educational, and religious fields. This study focuses on cognitive, affective, and psychomotor development in religion.